EFFECTS OF VARYING LEVELS OF DCAD WITH TWO LEVELS OF MG AND K ON ACID BASE STATUS, MG METABOLISM AND PRODUCTIVE PERFORMANCE OF BEETAL GOATS - U. Farooq; T. N. Pasha; M. A. Jabbar; M. Abdullah (Journal of Animal and Plant Sciences, 2014)
Thirty-six Beetal goats in early lactation were used in a 6-wk experiment with a 3 x 2 x 2 factorial arrangement of treatments. The objective was to reveal the effects of three levels of DCAD (-15, 2.5 and 20mEq/100g of feed DM) with two levels of K (1.35 and 2.0% of feed DM) and two levels of Mg (0.37 and 0.74%) in diets on productive performance. Increasing DCAD levels in diets significantly increased DMI, milk yield and milk fat percentage. Moreover, increasing K levels in diets increased milk yield of goats. However, increasing Mg levels in diets from 0.37% to 0.74% of feed DM negatively influenced the DMI intake, DM digestibility, milk yield and milk protein contents, as all the traits were reduced by increasing Mg levels. A linear increase in pH and HCO3− contents of blood and urine by increasing DCAD levels in diets evidenced a positive alteration in acid base status of the animals. However, K and Mg levels of diets showed no effect on same traits. Moreover, increasing K levels of diets reduced the Mg absorption. Similarly, higher Mg absorption, retention and balance were observed when added Mg was increased in diets. Overall, increasing DCAD levels in diets improved DMI and milk yield (3.5 and 11.1%, respectively), however, increasing Mg levels in diets showed negative effects on productive performance of Beetal goats.
Keywords: Dietarycation anion difference (DCAD); dry matter intake (DMI); Bicarbonate (HCO3−); magnesium (Mg); potassium (K); nitrogen (N)